Canal occlusion in cemented primary total hip replacement: autologous compacted bone block compared to a commercially available gelatine plug. Issue 3 (May 2021) - Agrawal, Pranshu; Chacko, Vinay J; Divecha, Hiren; Board, Tim N
Aims: To evaluate the stability of 2 canal occlusion systems; an autologous, compacted bone block and the biodegradable C-plug. We also sought to investigate any relationship between stability of the systems and the quality of cementation. A retrospective radiographic comparative review was conducted. Methods: A total of 203 consecutive patients were analysed, 89 received an autologous bone block and 114 had C-plugs. There was no significant differences between the groups in terms of age, sex and primary diagnosis. The mean cement tail length in the bone block group (6.42 mm; range 0–31) was significantly shorter than in the C-plug group (17.11 mm; range 0–65.7). Results: The proportion of patients with good quality of cementation (Barrack grade A) was significantly higher in the bone block group (80.6%) as compared to the C-plug group (56%) ( p  < 0.001). There was a negative correlation between the length of the cement tail and the Barrack grade, indicating that a short cement tail is associated with better quality cementation. Conclusions: We have shown that improved cement penetration and shorter cement tails can be achieved with the cheapest of all options for canal occlusion, an autologous compacted bone block and hence recommend this technique.